SMOKING RESTRICTIONS IN FEDERAL BUILDINGS AREN'T FAIR TO WORKERS - CLYBURN,J (Tufts Archival Research Center, 2007)
Article reporting on the ban on workplace smoking. Discusses the report by the Environmental Protection Agency (EPA) saying secondhand smoke can be toxic. Contends that the problem is not the secondhand smoke, but the poor ventilation systems in the buildings. Suggests that worksites invest in better ventilation and private smoking areas instead of banning smoking all together.